PELAKSANAAN PEMBERIAN KREDIT DENGAN JAMINAN PERJANJIAN FIDUSIA DI KOPERASI TANI NELAYAN ANDALAN KUTAI KARTANEGARA - sulaiman . (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
This study aims to determine the Legal Consequences of Fiduciary guarantee is not registered on Cooperative Farmers and Fishermen Mainstay. The formulation of the problem posed is: what if the Legal Consequences fiduciary assurance is not registered with the Registrar of Fiduciary? And how execution Assurances Fiduciary. If the collateral is not registered to the Fiduciary Registration Office? This study included Typology Normative legal research. Research Data collected by focusing the Things contained in the formulation of the problem. Resource persons who are parties to provide opinions, information or information on legal issues source used a Primary legal materials and secondary legal materials. The results of this study show that the Farmers and Fishermen Mainstay Cooperative lending money to customers with a range of nominal loan Rp.10.000.000,-million to Rp.25.000.000, - Fiduciary million bail. The loan with a nominal value above is not registered to the Fiduciary Registration Office because the lenders can charge. If the registered office to the cash redemption, Fiduciary registration will also be longer. The study recommends the need for warranty registration at the registration office Fiduciary to protect the interests of customers by the Bank as a debtor and its creditors.